Was bedeutet die Transformation der Märkte im digitalen Zeitalter? Ökonomische Grundlagen - Kundisch, Dennis; Gutt, Dominik (Digitale Ökonomie - Wie verändern sich die Märkte?)

Random-Walk-Hypothese - Gilroy, Bernard Michael; Volker, Seiler; Kröger, Sarah (wisu - das Wirtschaftsstudium)

Selling Value in Business Markets: Individual and Organizational Factors for Turning the Idea into Action - Terho, Harri; Eggert, Andreas; Ulaga, Wolfgang; Haas, Alexander; Boehm, Eva (Industrial Marketing Management)

The customer value proposition: evolution, development, and application in marketing - Payne, Adrian; Frow, Pennie; Eggert, Andreas (Journal of the Academy of Marketing Science)

Business service outsourcing in manufacturing firms: an event study - Eggert, Andreas; Boehm, Eva; Cramer, Christina (Journal of Service Management)

Service transition: A viable option for manufacturing companies with deteriorating financial performance? - Boehm, Eva; Eggert, Andreas; Thiesbrummel, Christoph (Industrial Marketing Management)

Visual Languages for Modeling Business Models: A Critical Review and Future Research Directions - John, Thomas; Kundisch, Dennis; Szopinski, Daniel (Proceedings of the 38th International Conference on Information Systems (ICIS), Seoul, South Korea)
A multiplicity of visual languages have been proposed for representing business models. These languages are claimed to facilitate tasks such as understanding, communicating, and innovating a business model; and have been developed rather independently by scholars from accounting, computer science, information systems, and strategy. Consequently, the existing approaches greatly differ and to some extent contradict each other, for example, regarding their understanding of the business model concept, their terminology, and their visual notations – which means there is little common ground for developing a cumulative stream of research. Therefore, we provide a systematic, cross-disciplinary review of this emerging field and synthesize the pragmatic, semantic, and syntactic foundations of the proposed approaches. Further, we derive an agenda for future research and discuss the challenges that lie ahead to advance the field.

Kundenwert

Renew or cancel? Drivers of customer renewal decisions for IT-based service contracts - Wangenheim, Florian v; Wünderlich, Nancy V; Schumann, Jan H (Journal of Business Research)
Manufacturers increasingly integrate information and communication technologies into their products so that they can provide IT-based services. Organizations that formerly concentrated on transactional sales thus confront a new challenge associated with managing service usage—retention and extracting value from investments in smart technology. This study combines a marketing and an information systems perspective in a field study conducted jointly with a large European car manufacturer. Understanding the renewal decision for IT-based service contracts requires knowledge from both disciplines. The paper shows that combining behavioral predictor variables stemming from marketing research and technology-related perceptual variables stemming from technology acceptance research increases the explanatory power and prediction accuracy of forecasting models for customer renewal decisions. Specifically, the authors show that perceptions of usefulness become more important the longer customers use IT-based services and the more services they use within the service contract.

Die zwei Perspektiven des Kundenwerts: Darstellung und Versuch einer Integration - Eggert, Andreas (Kundenwert)

Kundenwert – eine Einführung in die theoretischen und praktischen Herausforderungen der Bewertung von Kundenbeziehungen - Helm, Sabrina; Günter, Bernd; Eggert, Andreas (Kundenwert)

Renew or cancel? Drivers of customer renewal decisions for IT-based service contracts - Wangenheim, Florian v; Wünderlich, Nancy; Schumann, Jan H (Journal of Business Research)
Manufacturers increasingly integrate information and communication technologies into their products so that they can provide IT-based services. Organizations that formerly concentrated on transactional sales thus confront a new challenge associated with managing service usage—retention and extracting value from investments in smart technology. This study combines a marketing and an information systems perspective in a field study conducted jointly with a large European car manufacturer. Understanding the renewal decision for IT-based service contracts requires knowledge from both disciplines. The paper shows that combining behavioral predictor variables stemming from marketing research and technology-related perceptual variables stemming from technology acceptance research increases the explanatory power and prediction accuracy of forecasting models for customer renewal decisions. Specifically, the authors show that perceptions of usefulness become more important the longer customers use IT-based services and the more services they use within the service contract.
Keywords: IT-based service; Smart services; Contract renewal; Retention; Customer churn; Free trial

“Service Encounter 2.0”: An investigation into the roles of technology, employees and customers - Larivière, Bart; Bowen, David; Andreassen, Tor W; Kunz, Werner; Sirianni, Nancy J; Voss, Chris; Wünderlich, Nancy; De Keyser, Arne (Journal of Business Research)
The service encounter – one of the foundational concepts in service research – is fundamentally changing due to rapid evolutions in technology. In this paper, we offer an updated perspective on what we label the “Service Encounter 2.0”. To this end, we develop a conceptual framework that captures the essence of the Service Encounter 2.0 and provides a synthesis of the changing interdependent roles of technology, employees, and customers. We find that technology either augments or substitutes service employees, and can foster network connections. In turn, employees and customers are taking on the role of enabler, innovator, coordinator and differentiator. In addition, we identify critical areas for future research on this important topic.
Keywords: Service encounter; Technology roles; Employee roles; Customer roles; Employee experience; Customer experience

A Nice and Friendly Chat With a Bot: User Perceptions of AI-Based Service Agents - Wünderlich, Nancy; Paluch, Stefanie (Proceedings of the 38th International Conference on Information Systems (ICIS 2017))

How to Design Successful Gamification in Retail: The benefits and Pitfalls of Affordances - Teßmer, Isabel; Olsson, Marcus; Gustafsson, Anders; Wünderlich, Nancy (Proceedings of the 2017 Frontiers in Service Conference)

The Role of Contract Types for Employees’ Public Service Motivation - Grund, Christian; Thommes, Kirsten (Schmalenbach Business Review)

Age diversity and its effects on team performance - Klabuhn, Janny; Thommes, Kirsten (Academy of Management Proceedings)

Inklusive Bildung zwischen Beruflichkeit und Subjektorientierung - Eine Analyse ausbildungsvorbereitender Bildungsgänge - Frehe, Petra; Kremer, H.-Hugo (Potenzialorientierte Förderung in den Fachdidakten)

Kartellabsprachen und vertikale Preisbindungen - Eine wettbewerbspolitische Analyse am Bespiel der Lebensmittelindustrie in Deutschland - Niggemeyer, Laura

Acceptance of Mobile Learning at SMEs of the Service Sector - Beutner, Marc; Rüscher, Frederike Anna (Proceedings of the 13th International Conference Mobile Learning 2017)

Die Unterstützung von Entrepreneurship im Kultur- und Kreativsektor durch Berufsbildung - Beutner, Marc; Rüscher, Frederike Anna (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Green Economy und Green Entrepreneurship fördern – GET-UP Ergebnisse - Beutner, Marc; Rüscher, Frederike Anna (Kölner Zeitschrift für Wirtschaft und Pädagogik)

YES – Ein Online Gruppen-Deck-Card-Game zu European Citizenship - Beutner, Marc; Eggert, Denise; Rüscher, Frederike Anna (Hochschultage 2017)

Aktive Feedbacklösungen im Unterricht: Das Class-Room-Response-System PINGO - Beutner, Marc (Hochschultage 2017)

Webbasierte Classroom Response Systeme in der Hochschullehre – Eine designbasierte Fallstudie zur Unterstützung von Lehr-/Lernprozessen aus Studierendensicht - Beutner, Marc; Zoyke, A; Herrmann, P; Kundisch, Dennis; Magenheim, J; Neugebauer, J (Das Hochschulwesen)

Retourenmanagement zur Steigerung des Kundenwerts - Garnefeld, Ina; Boehm, Eva; Feider, Lena (Kundenwert)

Der Einfluss steuerlicher Verlustverrechnung auf Investitionsentscheidungen bei Risiko unter Berücksichtigung präskriptiver und deskriptiver Verhaltenselemente - Mehrmann, Annika

Die Bewertung der Steuerstrategie von Unternehmen - Brinkmann, Bastian

Die Initiative der EU zum öffentlichen Country-by-Country Reporting - Bornemann, Tobias; Eberhartinger, Eva (RWZ- Zeitschrift für Recht und Rechnungswesen)

Capital Charge Rates, Investment Incentives and Taxation - Bauer, Thomas; Kourouxous, Thomas (European Accounting Review)
This paper studies the impact of personal and corporate income taxation on capital charge rates in a delegation setting with a risk-averse manager. If the investment level influences the riskiness of the investment project, the capital charge rate deviates from the firm's cost of capital and depends crucially on the manager's personal income tax rate. Contradicting conventional wisdom, we find that a higher personal income tax rate induces higher investment expenditures and, surprisingly, increases the capital charge rate. The countervailing effect that a higher capital charge rate induces higher and not lower investment expenditures persists for pre-tax and after-tax performance measures as well as when the tax deductibility of managerial compensation is limited. Corporate income tax causes a similar effect only in the case of limited tax deductibility of compensation. Our insights remain valid regardless of the financing structure and the risk attitude of the investors.

Design and Evaluation of a Model-Driven Decision Support System for Repurposing Electric Vehicle Batteries - Klör, B; Monhof, M; Beverungen, Daniel; Bräuer, S (European Journal of Information Systems (EJIS))

End-of-Life Solutions für eCar-Batterien --- Entwicklung hybrider Leistungsbündel und Informationssysteme zur Entscheidungsunterstützung (EOL-IS) - Becker, Jörg; Monhof, Markus; Beverungen, Daniel; Bräuer, Sebastian; Klör, Benjamin; Plenter, Florian (Dienstleistungen als Erfolgsfaktor für Elektromobilität. Ergebnisse aus dem Förderschwerpunkt “Dienstleistungsinnovationen für Elektromobilität”)

Informationsmodellierung in Dienstleistungssystemen - Beverungen, Daniel; Matzner, Martin (Handbuch Dienstleistungsmanagement)

How to adequately relocate asylum applicants within the European Union - An attempt to apply matching theory in the current migration crisis - Streck, Thomas

Tying und Bundling in digitalen Märkten - eine wettbewerbspolitische Analyse - Winkelhake, Nikolai

The Technology Takeover - Sievers, Sönke; Kengelbach, Jens; Keienburg, Georg; Schmid, Timo; Gjersta, Ketil; Nielsen, Jesper; Walker, Decker

Rezension von: Bernd H. Oppermann/Jutta Stender-Vorwachs (Hrsg.): Autonomes Fahren – Rechtsfolgen, Rechtsprobleme, technische Grundlagen - Müller, Stefan (Zeitschrift zum Innovations- und Technikrecht (InTeR))

Legal Tech – for Legals or for Techies - Müller, Stefan (Zeitschrift zum Innovations- und Technikrecht (InTeR))

Rezension von: Stephan Breidenbach/Florian Glatz (Hrsg.): Rechtshandbuch Legal Tech, 2018, C.H. Beck. - Müller, Stefan (Zeitschrift zum Innovations- und Technikrecht (InTeR))

Hochautomatisierung jetzt, Vollautonomisierung später? - Müller, Stefan (Zeitschrift zum Innovations- und Technikrecht (InTeR))

Schranken urheberrechtlicher Befugnisse - Müller, Stefan (Urheberrecht und Internet)

Paying for Performance in Private Equity: Evidence from VC Partnerships - Hüther, Niklas; Robinson, David; Sievers, Sönke; Hartmann-Wendels, Thomas (SSRN Electronic Journal)
We offer the first empirical analysis connecting the timing of general partner (GP) compensation to private equity fund performance. Using detailed information on limited partnership agreements between private equity limited and general partners, we find that "GP-friendly" contracts - agreements that pay general partners on a deal-by-deal basis instead of withholding carried interest until a benchmark return has been earned - are associated with higher returns, both gross and net of fees. This is robust to measures of performance persistence, time period effects, and other contract terms, and is related to exit-timing incentives. Timing practices balance GP incentives against limited partner downside protection.
Keywords: venture capital; compensation; private equity; VC partnership; pay-performance relation

Innovationswettbewerbe im Internet - Teil 1 - Müller, Stefan (Zeitschrift zum Innovations- und Technikrecht (InTeR))

Innovationswettbewerbe im Internet – Teil 2 - Müller, Stefan; Wicker, Eva-Maria; Janicki, Thomas (Zeitschrift zum Innovations- und Technikrecht (InTeR))

Predicting Early Warning Signals of Financial Distress: Theory and Empirical Evidence - Klobucnik, Jan; Miersch, David; Sievers, Sönke (SSRN Electronic Journal)
This study proposes a simple theoretical framework that allows for assessing financial distress up to five years in advance. We jointly model financial distress by using two of its key driving factors: declining cash-generating ability and insufficient liquidity reserves. The model is based on stochastic processes and incorporates firm-level and industry-sector developments. A large-scale empirical implementation for US-listed firms over the period of 1980-2010 shows important improvements in the discriminatory accuracy and demonstrates incremental information content beyond state-of-the-art accounting and market-based prediction models. Consequently, this study might provide important ex ante warning signals for investors, regulators and practitioners.
Keywords: Financial distress prediction; probability of default; accounting information; stochastic processes; simulation

Towards Explaining the Popularity of the Business Model Canvas: A Dual-coding Approach - John, Thomas; Szopinski, Daniel (1st Business Model Conference)

Sick already? Job loss makes it even worse - Schmitz, Hendrik; Schiele, Valentin (Atlas of Science)

Preis, Service oder Leistungen: Was beeinflusst besonders die Krankenkassenwahl von gesetzlich Versicherten? - Schmitz, Hendrik (Krankenversicherung im Rating)

The Traveling Reviewer Problem – Exploring the Relationship Between Offline Locations and Online Rating Behavior - Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis (Proceedings of the 38th International Conference on Information Systems (ICIS))
Amongst the growing body of literature on the drivers of online ratings, the influence of customers’ local offline environment on their ratings has largely been neglected. This study examines the relationship between ratings made outside of a customer’s home area and the magnitude of online ratings. We employ a data-driven identification of a customer’s geographic home area and use variation in this variable to identify the consequences for the magnitude of ratings. In line with our theory, we find that customers who rate while traveling give, on average, higher ratings than locals. However, this relationship is moderated by the posting time of a review relative to consumption, as travelers post more negative ratings during or shortly after consumption. These relationships are most pronounced for customers who travel and rate less frequently. Our results come with substantial implications for a business’s average rating and for customer decision making.

Service Encounter 2.0": An Investigation Into the Roles of Technology, Employees and Customers. - Larivière, Bart; Bowen, David; Andreassen, Tor W; Kunz, Werner; Sirianni, Nancy J; Voss, Chris; Wünderlich, Nancy; De Keyser, Arne (Proceedings of QUIS 2017)

Do Companies Really Have to Emphasize the Triple Bottom Line? Analyzing the Effect of Competing Sustainable Market Orientations. - Becker-Özcamlica, Hürrem; Teßmer, Isabel; Wünderlich, Nancy (Proceedings of the 2017 Winter Marketing Educators' Conference)

The Traveling Reviewer Problem – Exploring the Relationship between Offline Locations and Online Rating Behavior - Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis (INFORMS Annual Meeting)

The Loyalty Effect of Gift Purchases - Eggert, Andreas; Steinhoff, Lena; Witte, Carina

Managing the Necessary Evil: Can Payment Methods Reduce Product Returns - Garnefeld, I; Boehm, E; Feider, L

Service Awards: Do They Help or Harm in Case of a Service Failure? - Cramer, C; Boehm, E; Eggert, A

Exploring the Scientific Impact of Information Systems Design Science Research: A Scientometric Study - Wagner, Gerit; Prester, Julian; Schryen, Guido (38th International Conference on Information Systems)
Design science is a fundamental research stream that contends its position in the information systems discipline. While ongoing debates address the relative importance of design science contributions in the information systems community, insights into the scientific impact of design science research (DSR) are missing and this lack of understanding arguably poses challenges to an informed discourse. To identify the most influential papers and those factors that explain their scientific impact, this paper presents an exploratory study of the scientific impact of DSR papers published in the AIS Senior Scholars' Basket of Journals. We uncover the current DSR landscape by taking stock of influential papers and theories and develop a model to explain the scientific impact of DSR papers. Our findings show that scientific impact is significantly explained by theorization and novelty. We discuss how the implications of our work can be projected on the overarching discourse on DSR.

Supporting Business Model Idea Generation Through Machine-generated Ideas: A Design Theory - John, Thomas (1st Business Model Conference)

High-Performance Business Computing - Effizienzsteigerung durch Parallelisierung - Schryen, Guido; Hristova, Diana (Smart Data Radar (Deutsche Bank))

Literature Reviews in IS Research: What Can Be Learnt from the Past and Other Fields? - Schryen, Guido; Benlian, Alexander; Rowe, Frantz; Shirley, Gregor; Larsen, Kai; Petter, Stacie; Paré, Guy; Wagner, Gerit; Haag, Steffi; Yasasin, Emrah (Communications of the AIS)
Literature reviews (LRs) are recognized for their increasing impact in the information systems literature. Methodologists have drawn attention to the question of how we can leverage the value of LRs to preserve and generate knowledge. The panelists who participated in the discussion of ?Standalone Literature Reviews in IS Research: What Can Be Learnt from the Past and Other Fields?? at ICIS 2016 in Dublin acknowledged this significant issue and debated a) what the IS field can learn from other fields and where IS-specific challenges occur, b) how the IS field should move forward to foster the genre of LRs, and c) what best practices are to train doctoral IS students in publishing LRs. This article reports the key takeaways of this panel discussion. Guidance for IS scholars is provided on how to conduct LRs that contribute to the cumulative knowledge development within and across the IS field to best prepare the next generation of IS scholars.
Keywords: Literature Review; Review Methodology; Research Methodology; Doctoral Training

A configuration-based recommender system for supporting e-commerce decisions - Scholz, Michael; Dorner, Verena; Schryen, Guido; Benlian, Alexander (European Journal of Operational Research)
Multi-attribute value theory (MAVT)-based recommender systems have been proposed for dealing with issues of existing recommender systems, such as the cold-start problem and changing preferences. However, as we argue in this paper, existing MAVT-based methods for measuring attribute importance weights do not fit the shopping tasks for which recommender systems are typically used. These methods assume well-trained decision makers who are willing to invest time and cognitive effort, and who are familiar with the attributes describing the available alternatives and the ranges of these attribute levels. Yet, recommender systems are most often used by consumers who are usually not familiar with the available attributes and ranges and who wish to save time and effort. Against this background, we develop a new method, based on a product configuration process, which is tailored to the characteristics of these particular decision makers. We empirically compare our method to SWING, ranking-based conjoint analysis and TRADEOFF in a between-subjects laboratory experiment with 153 participants. Results indicate that our proposed method performs better than TRADEOFF and CONJOINT and at least as well as SWING in terms of recommendation accuracy, better than SWING and TRADEOFF and at least as well as CONJOINT in terms of cognitive load, and that participants were faster with our method than with any other method. We conclude that our method is a promising option to help support consumers' decision processes in e-commerce shopping tasks.
Keywords: E-Commerce; Recommender System; Attribute Weights; Configuration System; Decision Support

Forschung in Innovationsarenen - Formate und Reflexionen einer gestaltungsorientierten Berufsbildungsforschung - Kremer, H.-Hugo; Frehe, Petra; Kückmann, Marie-Ann; Kundisch, Heike (bwp@ Berufs- und Wirtschaftspädagogik - online)

Qualifizierungsbausteine in ausbildungsvorbereitenden Bildungsgängen am Berufskolleg - Kremer, H.-Hugo; Frehe, Petra (Berufsbildung)

Internationale Förderklassen an Berufskollegs. Ein ausbildungsvorbereitendes Anegbot!? - Frehe, Petra; Kremer, H.-Hugo (Berufsschullehrerbildung in der Volksrepublik China und in der Bundesrepublik Deutschland. Professionalisierung - Kompetenzen - Herausforderungen)

Berufskollegübergreifende Entwicklungsverbünde - Innovationen für eine nachhaltige Bildungsarbeit vor Ort - Kremer, H.-Hugo; Frehe, Petra (Berufsbildung für eine nachhaltige Entwicklung auf dem Weg in den (Unterrichts-)Alltag: Wie können Vernetzungsaktivitäten die Implementation unterstützen?)

Conceptualizing smart service systems - Beverungen, Daniel; Müller, Oliver; Matzner, Martin; Mendling, Jan; vom Brocke, Jan (Electronic Markets)

The effects of competition on medical service provision - Brosig-Koch, Janet; Hehenkamp, Burkhard; Kokot, Johanna (Health Economics)
We explore how competition between physicians affects medical service provision. Previous research has shown that, without competition, physicians deviate from patient‐optimal treatment under payment systems like capitation and fee‐for‐service. Although competition might reduce these distortions, physicians usually interact with each other repeatedly over time and only a fraction of patients switches providers at all. Both patterns might prevent competition to work in the desired direction. To analyze the behavioral effects of competition, we develop a theoretical benchmark that is then tested in a controlled laboratory experiment. Experimental conditions vary physician payment and patient characteristics. Real patients benefit from provision decisions made in the experiment. Our results reveal that, in line with the theoretical prediction, introducing competition can reduce overprovision and underprovision, respectively. The observed effects depend on patient characteristics and the payment system, though. Tacit collusion is observed and particularly pronounced with fee‐for‐service payment, but it appears to be less frequent than in related experimental research on price competition.

Location Choice and Quality Competition in Mixed Hospital Markets - Hehenkamp, Burkhard; Kaarboe, Oddvar

Evolutionary Equilibrium in Stochastic Contests - Entry, Effort, and Overdissipation - Gu, Yiguan; Hehenkamp, Burkhard; Leininger, Wolfgang

Asymmetric Dominance Effect with Multiple Decoys for Low- and High-Variance Lotteries - Sürücü, Oktay; Mir Djawadi, Behnud; Brangewitz, Sonja

The revenue potential of product differentiation: Empirical evidence fro the Croation restaurant industry - Frick, Bernd; Gergaud, Olivier; Winter, Petra (Gastronomy and Tourism)

Zu den Wechselwirkungen von Wettbewerb und Innovation - Eine ökonomische Analyse - Petersen, Henning Cornelius

Zu den Anreizwirkungen der Kronzeugenregelung - Eine spieltheoretische Analyse - Turan, Alparslan

Zu den Anreiz- und Wohlfahrtswirkungen der Kronzeugenregelung - Das Fallbeispiel des LKW-Kartells (1997-2011) - Iding, Jerome

Vertikale Wettbewerbsbeschränkung auf Hotelreservierungsportalen - eine ökonomische Analyse anhand der Bestpreisklausel von Booking - Lütkevedder, Dennis

Open Innovation - Eine ökonimische Perspektive - Laudage, Felix

Marktmacht in zweiseitigen Online-Märkten - Probleme der Bestimmung einer marktbeherrschenden Stellung am Beispiel von eBay - Goebel, Marion

Marktabgrenzung in der Internetökonomie - Ein Fallbeispiel zum Fusionsantrag von Immowelt und Immonet - Wagemeyer, Marleen

Die Fusion von AOL und Time Warner - Eine wettbewerbspolitische Analyse - Shabani, Albana

Uncertainties as Barriers for Knowledge Sharing with Enterprise Social Media - Trier, Matthias; Fung, Magdalene; Hansen, Abigail (25th European Conference on Information Systems, ECIS 2017, Guimarães, Portugal, June 5-10, 2017)

Das Zusammenschlussvorhaben von Edeka und Kaiser's Tengelmann - eine ökonomische Analyse - Hamacher, Dustin Stefan

Matching Strategies of Heterogeneous Agents under Incomplete Information in a University Clearinghouse - Hoyer, Britta; Stroh-Maraun, Nadja
In actual school choice applications the theoretical underpinnings of the Boston School Choice Mechanism (BM) (complete information and rationality of the agents) are often not given. We analyze the actual behavior of agents in such a matching mechanism, using data from the matching mechanism currently used in a clearinghouse at a faculty of Business Administration and Economics at a German university, where a variant of the BM is used, and supplement this data with data generated in a survey among students who participated in the clearinghouse. We find that under the current mechanism over 70% of students act strategically. Controlling for students' limited information, we find that they do act rationally in their decision to act strategically. While students thus seem to react to the incentives to act strategically under the BM, they do not seem to be able to use this to their own advantage. However, those students acting in line with their beliefs manage a significantly better personal outcome than those who do not. We also run simulations by using a variant of the deferred acceptance algorithm, adapted to our situation, to show that the use of a different algorithm may be to the students' advantage.

Making Gamification Easy for the Professor: Decoupling Game and Content with the StudyNow Mobile App - Feldotto, Matthias; John, Thomas; Kundisch, Dennis; Hemsen, Paul; Klingsieck, Katrin; Skopalik, Alexander (Proceedings of the 12th International Conference on Design Science Research in Information Systems and Technology (DESRIST))
Many university students struggle with motivational problems, and gamification has the potential to address these problems. However, gamification is hardly used in education, because current approaches to gamification require instructors to engage in the time-consuming preparation of their course contents for use in quizzes, mini-games and the like. Drawing on research on limited attention and present bias, we propose a "lean" approach to gamification, which relies on gamifying learning activities (rather than learning contents) and increasing their salience. In this paper, we present the app StudyNow that implements such a lean gamification approach. With this app, we aim to enable more students and instructors to benefit from the advantages of gamification.

Towards a Lean Approach for Gamifying Education - John, Thomas; Feldotto, Matthias; Hemsen, Paul; Klingsieck, Katrin; Kundisch, Dennis; Langendorf, Mike (Proceedings of the 25th European Conference on Information Systems (ECIS))
Many university students struggle with motivational problems, and gamification has the potential to address these problems. However, using gamification currently is rather tedious and time-consuming for instructors because current approaches to gamification require instructors to engage in the time-consuming preparation of course contents (e.g., for quizzes or mini-games). In reply to this issue, we propose a “lean” approach to gamification, which relies on gamifying learning activities rather than learning contents. The learning activities that are gamified in the lean approach can typically be drawn from existing course syllabi (e.g., attend certain lectures, hand in assignments, read book chapters and articles). Hence, compared to existing approaches, lean gamification substantially lowers the time requirements posed on instructors for gamifying a given course. Drawing on research on limited attention and the present bias, we provide the theoretical foundation for the lean gamification approach. In addition, we present a mobile application that implements lean gamification and outline a mixed-methods study that is currently under way for evaluating whether lean gamification does indeed have the potential to increase students’ motivation. We thereby hope to allow more students and instructors to benefit from the advantages of gamification.

Achieving more by saying less? On the Moderating Effect of Information Cues in Paid Search - Schlangenotto, Darius; Kundisch, Dennis (Proceedings of the 50th annual Hawaii International Conference on System Sciences (HICSS), Waikoloa Village, HI, USA)
Research on ad copy design is well-studied in the context of offline marketing. However, researchers have only recently started to investigate ad copies in the context of paid search, and have not yet explored the potential of information cues to enhance customers’ search process. In this paper we analyze the impact of an information cue on user behavior in ad copies. Contrary to prevalent advice, results suggest that reducing the number of words in an ad is not always beneficial. Users act quite differently (and unexpectedly) in response to an information cue depending on their search phrases. In turn, practitioners could leverage the observed moderating effect of an information cue to enhance paid search success. Furthermore, having detected deviating user behavior in terms of clicks and conversions, we provide first indicative evidence of a self-selection mechanism at play when paid search users respond to differently phrased ad copies.

Achieving More by Paying Less? How Bricks-and-Mortar Retailers Can Benefit by Bidding Less Aggressively in Paid Search - Schlangenotto, Darius; Kundisch, Dennis; Gutt, Dominik (Proceedings of the 38th International Conference on Information Systems (ICIS), Seoul, South Korea)
Current research on paid search highlights its ability to enhance both online and offline conversions. Yet, research investigating the impact of placing paid search ads on less prominent positions on subsequent consumer behavior is limited to the online environment. This paper presents a field experiment using differences-in-differences analysis to investigate whether the targeting of a less prominent ad position can be beneficial for bricks-and-mortar retailers. Results indicate that paid search advertising budgets could be allocated more efficiently by targeting less prominent ad positions, thus allowing bricks-and-mortar retailers with a limited marketing budget to increase the reach of their marketing campaign, attract more consumers to their website and achieve an overall increase in conversions. Furthermore, the pay-per-click billing mechanism allows advertisers to increase their marketing reach at no additional cost. Consequently, bricks-and-mortar retailers should consider targeting less prominent ad positions to reduce advertising costs while simultaneously enhancing advertising benefits.

A Variability Model for Store-oriented Software Ecosystems: An Enterprise Perspective (Supplementary Material) - Jazayeri, Bahar; Zimmermann, Olaf; Engels, Gregor; Kundisch, Dennis

A Variability Model for Store-oriented Software Ecosystems: An Enterprise Perspective - Jazayeri, Bahar; Zimmermann, Olaf; Engels, Gregor; Kundisch, Dennis (Proceedings of the 15th International Conference on Service Oriented Computing (ICSOC))
Pioneers of today’s software industry like Salesforce and Apple have established successful ecosystems around their software platforms. Architectural knowledge of the existing ecosystems is implicit and fragmented among online documentation. In protection of intellectual property, existing documentation hardly reveals influential business strategies that affect the ecosystem structure. Thus, other platform providers can hardly learn from the existing ecosystems in order to systematically make reasonable design decisions with respect to their business strategies to create their own ecosystems. In this paper, we identify a variability model for architectural design decisions of a store-oriented software ecosystem product line from an enterprise perspective, comprising business, application, and infrastructure views. We derive the variability model from fragmentary material of existing ecosystems and a rigorous literature review using a research method based on the design science paradigm. To show its validity, we describe real-world ecosystems from diverse domains using the variability model. This knowledge helps platform providers to develop customized ecosystems or to recreate existing designs in a systematic way. This, in turn, contributes to an increase in designer and developer productivity.

A Homeowner’s Guide to Airbnb: Theory and Empirical Evidence for Optimal Pricing Conditional on Online Ratings - Neumann, Jürgen; Gutt, Dominik (Proceedings of the 25th Conference on Information Systems (ECIS))
Optimal price setting in peer-to-peer markets featuring online ratings requires incorporating interactions between prices and ratings. Additionally, recent literature reports that online ratings in peer-to-peer markets tend to be inflated overall, undermining the reliability of online ratings as a quality signal. This study proposes a two-period model for optimal price setting that takes (potentially inflated) ratings into account. Our theoretical findings suggest that sellers in the medium-quality segment have an incentive to lower first-period prices to monetize on increased second-period ratings and that the possibility on monetizing on second-period ratings depends on the reliability of the rating system. Additionally, we find that total profits and prices increase with online ratings and additional quality signals. Empirically, conducting Difference-in-Difference regressions on a comprehensive panel data set from Airbnb, we can validate that price increases lead to lower ratings, and we find empirical support for the prediction that additional quality signals increase prices. Our work comes with substantial implications for sellers in peer-to-peer markets looking for an optimal price setting strategy. Moreover, we argue that our theoretical finding on the weights between online ratings and additional quality signals translates to conventional online markets.

Simulating Storage Policies for an Automated Grid-Based Warehouse System - Beckschäfer, Michaela; Malberg, Simon; Tierney, Kevin; Weskamp, Christoph (Lecture Notes in Computer Science)

Financial penalties and bank performance - Köster, Hannes; Pelster, Matthias (Journal of Banking & Finance)

The determinants of CDS spreads: evidence from the model space - Pelster, Matthias; Vilsmeier, Johannes (Review of Derivatives Research)

I’ll Have What S/he’s Having: A Case Study of a Social Trading Network - Pelster, Matthias (Proceedings of the International Conference on Information Systems)
Opinion leaders of an investment network can have a significant impact on capital mar-kets because their investment decisions are adopted by their peers and trigger large trad-ing cascades, increasing herding behavior and comovement among stock returns. This paper analyzes the interaction-based relations of traders from a large social trading plat-form and identifies the driving forces and the opinion leaders within a large online trading network as the nodes with the highest centrality and the highest force of infection, respec-tively. Relying on recent insights from epidemiological research, I maintain that central-ity identifies the most central traders in the network, while the expected force quantifies the most influential traders and their spreading power. I study the behavior and charac-teristics that set central and influential traders apart from other traders. The ability to identify focal points and their trading behavior within a trading network is important for investors, investment advisers, and policy makers.
Keywords: Online trading; investment advice; network modeling; Expected Force; herding.

Enterprise Social Networks: Neue Tools für das Informations und Wissensmanagement - Winkler, Till J.; Trier, Matthias (Tools revisited – Rationalität und Kreativität durch Management-Tools?)
Enterprise Social Networks (ESNs), d. h. Informationssysteme, die die Vernetzung von Mitarbeitern in Unternehmen fördern sollen, sind in verschiedenen Varianten und unter verschiedenen Bezeichnungen (etwa Enterprise Social Media, Corporate Social Software, Social Business oder Enterprise 2.0) bereits seit etwa gut einem Jahrzehnt auf dem Markt. Dennoch erfreuen sie sich erst seit den letzten Jahren steigender Beliebtheit und halten ebenfalls nach und nach flächendeckenden Einzug in Großunternehmen wie Siemens, Daimler oder Deutsche Telekom. Um mit dem Gartner »Hype Cycle« zu argumentieren: Das Thema ESN hat die Spitze des Hypes längst überschritten, das »Tal der Enttäuschungen« durchschritten und nähert sich nun zunehmend dem »Plateau der Produktivität«. Motivation genug, um sich anhand einiger ausgewählter Fallbeispiele mit ESNs genauer auseinanderzusetzen.

Value Co-creation in the Digital Factory: The Empowered Role of Shop Floor Workers - Richter, Shahper; Trier, Matthias; Richter, Alexander

Innovations, growth and participation in advanced economies - a review of major concepts and findings - Gries, T.; Grundmann, R.; Palnau, Irene; Redlin, Margarete (International Economics and Economic Policy)

Does Price Framing Affect the Consumer Price Sensitivity of Health Plan Choice? - Schmitz, Hendrik; Ziebarth, Nicolas R. (Journal of Human Resources)

Informal Care and Long-term Labor Market Outcomes - Schmitz, Hendrik; Westphal, Matthias (Journal of Health Economics)

On the interdependence of ambulatory and hospital care in the German health system - Büyükdurmus, Tugba; Kopetsch, Thomas; Schmitz, Hendrik; Tauchmann, Harald (Health Economics Review)

Multi-Dimensional Bargaining Problem and Nash Solution - A procedural approach - N, N

Game Theory solutions for the Transshipment Problem in Logistic Networks - N, N